2013
DOI: 10.1134/s0006297913020089
|View full text |Cite
|
Sign up to set email alerts
|

Action of two phospholipases A2 purified from Bothrops alternatus snake venom on macrophages

Abstract: The in vitro effects of BaltTX-I, a catalytically inactive Lys49 variant of phospholipase A2 (PLA2), and BaltTX-II, an Asp49 catalytically active PLA2 isolated from Bothrops alternatus snake venom, on thioglycollate-elicited macrophages (TG-macrophages) were investigated. At non-cytotoxic concentrations, the secretory PLA2 BaltTX-I but not BaltTX-II stimulated complement receptor-mediated phagocytosis. Pharmacological treatment of TG-macrophages with staurosporine, a protein kinase C (PKC) inhibitor, showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 41 publications
2
14
0
4
Order By: Relevance
“…The authors showed that MT-II, a Lys-49 isolated from the venom of Bothrops asper , also considerably increases phagocytosis via the complement receptor, while MT-III, an Asp-49, only stimulates phagocytosis via mannose receptors. Similar results were obtained by Setúbal et al [19]. These authors showed that BaltTX-I, a Lys49, but not BaltTX-II, an Asp-49 enzyme, is able to directly stimulate phagocytosis via the complement receptor.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The authors showed that MT-II, a Lys-49 isolated from the venom of Bothrops asper , also considerably increases phagocytosis via the complement receptor, while MT-III, an Asp-49, only stimulates phagocytosis via mannose receptors. Similar results were obtained by Setúbal et al [19]. These authors showed that BaltTX-I, a Lys49, but not BaltTX-II, an Asp-49 enzyme, is able to directly stimulate phagocytosis via the complement receptor.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, for the realization of the other proposed experiments, the highest concentration, 6  μ g/mL, was chosen. It is noteworthy that the same concentration was used in the study of macrophage activation by Zuliani et al [12] and Setúbal et al [19]. The three PLA 2 s used had the same effect on macrophages.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The release of histamine from mast cells has been proposed to be a mechanism of snake venom PLA2-induced local inflammation (Cirino et al, 1989;Teng, 1990, Landucci et al, 1998). Some group II snake venom PLA2 are able to recruit and activate leukocytes (Zuliani et al, 2005b, Moreira et al, 2011, Setúbal et al, 2013, Furtado et al, 2014, but there are only few reports on the action of group I snake venom PLA2. Naja m. mocambique PLA2 induced dose-and time-dependent cellular infiltration into the rat pleural cavity (Weichman et al, 1989).…”
Section: Discussionmentioning
confidence: 99%